Integration of Sharia in Zakat Law (UIN Sunan Kudus, 2021)
Law No. 23 of 2011 on Zakat Management, which is abbreviated as the Law of Zakat Management, places Islamic law as a principle for the management of zakat, which means that every zakat amil in the planning, application, and coordination of collection, allocation of resources must always be based on the regulations of Islamic law. The aim of the writing of this article is to explain the existence of zakat in Islamic law and the law on the management of zakat, Law No. 23 of 2011 as an ius constitutum, and the integration of Islamic law in the law of zakat management. This article can be categorized as a type of research in the library. The method of approach used is a qualitative approach. In addition to a qualitative approach, a normative legal approach is also used in the discussion of this article. The data source used is secondary data, consisting of primary legal materials, secondary legal materials, and tertiary judicial materials. The results of the study show that the existence of zakat in Islamic law and the Law of Zakat Management is an important pillar in building the values of devotion to Allah SWT, justice, and community welfare. The passage of Law No. 23 of 2011 is an inseparable part of the current national legal system (ius constitutum) and the integration of Islamic law in the law of zakat management is reflected in the preamble and in the provisions of Clause 2 of Law No. 23 of 2011 which lay down Islamic law as a principle for the management of Zakat.